Lactose hydrolyzing activity of the lactase immobilized polycaprolactone and silk fibroin-based nanofiber and nitrocellulose membrane - AKBAY, TUĞBA (My University, 2022)
© 2022 Elsevier LtdThis study aimed to investigate the activity of lactase immobilized polycaprolactone and silk fibroin (PCL/SF)-based nanofiber and nitrocellulose membrane for the preparation of lactose-reduced milk. PCL/SF -based nanofiber was prepared by using the electrospinning method. The lactase enzyme was immobilized using the physical adsorption method on both surfaces, and then the optimum operating temperature and pH of the immobilized enzymes were determined. The efficiency of the immobilized lactase enzyme was determined in both goat and cow milk. The nutrient content of milk was also analyzed before and after the incubation of nanofiber and membrane with milk. The lactose hydrolysis efficiency of the lactase immobilized nitrocellulose membrane was found to be higher than the lactase immobilized PCL/SF -based nanofiber. Lactose was hydrolyzed 59% in cow milk and 87% in goat milk by using lactase immobilized nitrocellulose membrane. 42% of lactose was also hydrolyzed in cow milk and 21% was hydrolyzed in goat milk by using lactase immobilized PCL/SF-based nanofiber. However, the use of these two bioactive surfaces did not change the fat and protein composition of both cow and goat milk. In conclusion, lactase immobilized nitrocellulose membrane was found to be more advantageous in the production of lactose-reduced milk than the lactase immobilized polycaprolactone/silk fibroin nanofiber.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Yaşam Bilimleri (LIFE); Tarım Bilimleri; Moleküler Biyoloji ve Genetik; GIDA BİLİMİ VE TEKNOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Agriculture & Environment Sciences (AGE); Life Sciences (LIFE); AGRICULTURAL SCIENCES; MOLECULAR BIOLOGY & GENETICS; FOOD SCIENCE & TECHNOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Yemek bilimi; Biyokimya; Food Science; Biochemistry; Lactose reduced milk; Immobilization; Bioactive surface; Electrospinning; Lactose intolerance; BETA-GALACTOSIDASE; LIPASE; IMPACT